2019
DOI: 10.1007/s40368-019-00464-2
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on the use of fluoride for caries prevention in children: an updated EAPD policy document

Abstract: Aim To update the exisitng European Academy of Paediatric Dentistry (EAPD) 2009 fluoride guidelines. Methods Experts met in Athens, Greece duirng November 2018 for the following groups: I Fluoride toothpastes, II Fluoride gels, rinses and varnishes, III Fluoridated milk, fluoridated salt, tablets/lozenges and drops, IV Water fluoridation. Systematic reviews and meta-analyses were reviewed and discussed for each of the groups. The GRADE system was used to assess the quality of evidence which was judged as HIGH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
163
0
21

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(186 citation statements)
references
References 59 publications
2
163
0
21
Order By: Relevance
“…It is encouraging that the majority of the dentists that took part in this study reported that they would use fissure sealants and fluoride varnish in high-risk children. Although these findings are self-reported and, therefore, do not necessarily guarantee that the participants use these treatments in their clinics, they show that GDPs in Jordan are aware of the importance of sealants (Ahovuo-Saloranta et al 2007) and fluoride varnish (Toumba et al 2019) in caries prevention. GDPs in this study cited parental awareness and child cooperation as barriers that hinder their delivery of preventive treatment.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It is encouraging that the majority of the dentists that took part in this study reported that they would use fissure sealants and fluoride varnish in high-risk children. Although these findings are self-reported and, therefore, do not necessarily guarantee that the participants use these treatments in their clinics, they show that GDPs in Jordan are aware of the importance of sealants (Ahovuo-Saloranta et al 2007) and fluoride varnish (Toumba et al 2019) in caries prevention. GDPs in this study cited parental awareness and child cooperation as barriers that hinder their delivery of preventive treatment.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, only a few indicated that they would take a tailored approach to dietary counselling, including the use of diet diaries and practical advice on reducing sugar intake frequency or limiting it to mealtimes. Furthermore, none of the participants mentioned that they would advise the family on toothpaste fluoride concentration or spitting but not rinsing after brushing, despite those being evidencebased approaches to increasing fluoride exposure and reducing caries risk (Chestnutt et al 1998;Public Health England 2014;Toumba et al 2019). Previous studies in developed countries Pearce and Catleugh 2013) and other developing countries (Wagle et al 2017) noticed a similar trend in reported oral health education delivery.…”
Section: Discussionmentioning
confidence: 94%
“…The amount of 0.125 grams (grain of rice size) is recommended in babies and 0.25 grams (pea size) in children. The EAPD also suggests that children over 6 years old use toothpaste containing 1450 ppmF covering the length of the toothbrush (0.5-1.0 grams) [13].…”
Section: The Current Guidelines Of American Academy Of Pediatric Dentmentioning
confidence: 99%
“…2 Systematic reviews have shown that only toothpastes with fluoride concentrations of at least 1000 ppm can prevent caries effectively. 4 The typical fluoride concentration of regular toothpaste is approximately 1000-1500 ppm. 2 Unlike individual measures, PFA is usually carried out by professional dentists or participants, including forms of gel, foam and varnish.…”
Section: Description Of the Interventionmentioning
confidence: 99%
“…Open access other fluorine-containing vehicles, care must be taken regarding the cumulative fluoride exposure of children under 6 years of age. 4 Additionally, cost-effectiveness must be considered for groups with low caries prevalence. 10 Regarding efficacy and adverse effects, is it necessary for children to receive PFA in addition to regular fluoride toothpaste?…”
Section: Introduction Backgroundmentioning
confidence: 99%